2023
DOI: 10.3390/rs15051290
|View full text |Cite
|
Sign up to set email alerts
|

Hazard Potential in Southern Pakistan: A Study on the Subsidence and Neotectonics of Karachi and Surrounding Areas

Abstract: Coastal communities in deltaic regions worldwide are subject to subsidence through a combination of natural and anthropogenic processes. The city of Karachi in southern Pakistan is situated along the diffuse western boundary of the tectonically active Indian Plate, making it more susceptible to natural subsidence processes from plate motion-related deformational events such as earthquakes and faulting. Karachi has a dense population of over 16 million people, and determining the rate of subsidence and extent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…11 and 7). According to previous study works (Amin, Shahzad et al 2022, Kanwal, Ding et al 2022, Tirmizi, Khan et al 2023, this is especially concerning given the substantial high-rise building and housing community construction on the reclaimed ground, and continued unchecked expansion could have disastrous outcomes. Soil liquefaction and construction load could be one of the main triggers for deformation in the study area.…”
Section: In Uence Of Urban Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…11 and 7). According to previous study works (Amin, Shahzad et al 2022, Kanwal, Ding et al 2022, Tirmizi, Khan et al 2023, this is especially concerning given the substantial high-rise building and housing community construction on the reclaimed ground, and continued unchecked expansion could have disastrous outcomes. Soil liquefaction and construction load could be one of the main triggers for deformation in the study area.…”
Section: In Uence Of Urban Developmentmentioning
confidence: 99%
“…The main possible cause of excessive groundwater abstraction is brought on by rapid urbanization and a rise in the need for water for domestic and industrial uses. Municipal water supplies are becoming increasingly scarce, which has led to a signi cant reliance on groundwater extraction through private wells and communal wells(Tirmizi, Khan et al 2023). Inadequate water supply has led to overuse of groundwater in the coastal areas of Clifton and DHA, which is expected to result in subsidence along the state highways(Kanwal, Ding et al 2022), and these zones were found to be highly deforming in this study too.…”
mentioning
confidence: 99%
“…We calculate an InSAR deformation gradient to determine the areas that are most at risk of infrastructure damage (Figure 12). Previous studies have shown that an InSAR gradient map can be an effective tool in determining the areas that require careful monitoring for infrastructure damage [69,71]. In summary, in this work, for the first time, full resolution InSAR data are analyzed to assess and understand subsidence in Katy, a sprawling suburban area located west of Houston.…”
Section: Risk To Infrastructurementioning
confidence: 99%
“…Remote Sens. 2023, 15, x FOR PEER REVIEW 16 of 20tool in determining the areas that require careful monitoring for infrastructure damage[69,71].…”
mentioning
confidence: 99%